THE ANALYSIS OF USING PARTS OF SPEECH IN DESCRIPTIVE PARAGRAPH - Surista, Ade; Setiawan, Wawan (Sekolah Tinggi Bahasa Asing JIA, 2025)
Writing is an activity used to communicate ideas clearly through appropriate words arranged in written form, especially in composing descriptive texts. This research aimed to describe how the students use parts of speech in their writing descriptive paragraph. The sample uses the students of semester II morning class with the total number of students are 35 students. The instrument uses in this research are test and interview. In semester II, the students should be able to use parts of speech in developing descriptive writing. The result shows that from the first test, the average is 84.2. In the second test, from 35 students, there are 12 students do all correct sentences. There are 12 students made12 mistakes in nouns. For pronouns, there are 2 students who made 2 mistakes. and in verbs, there are 13 students who made 24 mistakes.